2019
DOI: 10.1089/cap.2018.0140
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Related Comorbidities in Childhood-Onset Obsessive Compulsive Disorder: Lifetime Prevalence in the Obsessive Compulsive Disorder Collaborative Genetics Association Study

Abstract: Objective: To evaluate the lifetime prevalence of infectious, inflammatory, and autoimmune disorders in a multisite study of probands with childhood-onset obsessive compulsive disorder (OCD) and their first-degree relatives.Methods: Medical questionnaires were completed by 1401 probands and 1045 first-degree relatives in the OCD Collaborative Genetics Association Study. Lifetime prevalence of immune-related diseases was compared with the highest available population estimate and reported as a point estimate wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 76 publications
1
18
0
Order By: Relevance
“…Epidemiologic studies from Sweden and North America have consistently shown familial clustering of immune-mediated diseases in patients with OCD and tic disorders (Murphy et al 2010;Mataix-Cols et al 2018;Westwell-Roper et al 2019). Our findings of an increased risk of having immune-mediated disorders in firstdegree relatives of our patients with early abrupt-onset OCD are in line with those of Westwell-Roper et al (2019) in the general OCD population. When seeing patients with both abrupt-onset OCD and idiopathic OCD, clinicians should carefully evaluate families for immune disorders.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Epidemiologic studies from Sweden and North America have consistently shown familial clustering of immune-mediated diseases in patients with OCD and tic disorders (Murphy et al 2010;Mataix-Cols et al 2018;Westwell-Roper et al 2019). Our findings of an increased risk of having immune-mediated disorders in firstdegree relatives of our patients with early abrupt-onset OCD are in line with those of Westwell-Roper et al (2019) in the general OCD population. When seeing patients with both abrupt-onset OCD and idiopathic OCD, clinicians should carefully evaluate families for immune disorders.…”
supporting
confidence: 86%
“…To the Editor: W e read with interest your June 2019 publication regarding the multi-site questionnaire study by Westwell-Roper et al (2019). The authors reported increased rates of immunemediated comorbidities among first-degree relatives of patients with obsessive compulsive disorder (OCD).…”
mentioning
confidence: 99%
“…There is also limited knowledge on whether the characteristics of tics and OCS may differ depending on prior/current exposure to infections. A recent report showed that young OCD patients with higher frequency of self-reported ear or throat infections have increased severity of cleaning/contamination-related symptoms ( 72 ), although an altered perception of their medical history and subsequent over-reporting might also explain this finding.…”
Section: Risk Factors For Immune Dysregulationmentioning
confidence: 99%
“…A potential limitation of this work is the likely under-representation of OCD patients who do not seek medical help. In relation to this, Westwell-Roper et al ( 72 ) published the largest to date clinic-based survey that estimated the lifetime prevalence of immune-related diseases using self-report medical questionnaires from 1,401 youth with OCD and 1,045 of their first-degree relatives enrolled in the OCD Collaborative Genetics Association Study. This descriptive study was limited by the lack of a control population, reliance on retrospective self-report and post-hoc evaluation of questionnaires that did not screen for all autoimmune comorbidities.…”
Section: Comorbidity With Immune-mediated Illnesses ( Tablementioning
confidence: 99%
“…In the pediatric population, OCD has been linked to some antibodies for streptococcal infections, which can cross-react with other epitopes found on the neurons of the basal ganglia. Most commonly, this cross-reaction results in pediatric acute-onset neuropsychiatric syndrome (PANS) as well as pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections (PANDAS) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%